Cost-effectiveness and public health impact of recombinant zoster vaccine versus no herpes zoster vaccination in selected populations of immunocompromised adults in Canada - Sydney George; Justin Carrico; Katherine A. Hicks; Dessi Loukov; Cheryl Ng; Desmond Curran (BMC Health Services Research)
Abstract Background The risk of herpes zoster (HZ) increases with age and in immunocompromised (IC) patients. Recombinant zoster vaccine (RZV) is currently recommended in Canada for people aged ≥ 50 years. The objectives of the current study were to evaluate the cost-effectiveness and public health impact of RZV versus no HZ vaccination in select Canadian IC adult populations. Methods The ZOster ecoNomic Analysis ImmunoCompromised (ZONA IC) model followed a base-case cohort of 1600 patients with hematopoietic stem-cell transplant (HSCT) from a starting age of 55 years, who maintained IC status for 5 years, from a societal perspective. Scenario analyses were conducted for patients with breast cancer, renal transplant, human immunodeficiency virus (HIV), and Hodgkin lymphoma. These probabilistic analyses used a life-long time horizon and discount rates of 1.5% for costs and quality-adjusted life-years (QALYs). First-dose coverage was assumed to be 60% and second-dose completion 100%. Deterministic one-way sensitivity analysis for the base case was performed. Costs are reported in 2022 Canadian dollars, with an assumed cost-effectiveness threshold of $50,000 per QALY gained. Results In the base-case analysis (HSCT), it was estimated that RZV would prevent medians of 116 HZ and 27 postherpetic neuralgia (PHN) cases, respectively versus no HZ vaccination. Estimated median numbers needed to vaccinate were 8 and 35 to avoid one HZ and one PHN case, respectively. The median incremental cost-effectiveness ratio (ICER) was $22,648 per QALY gained and was most sensitive to assumptions of HZ incidence, direct medical costs for unvaccinated HZ without PHN, and RZV efficacy against PHN. In other IC populations, estimated median ICERs were $24,328 (breast cancer), $27,237 (renal transplant), $67,207 (HIV), and $81,470 (Hodgkin lymphoma). Conclusions RZV in Canada improves public health outcomes and is likely cost-effective for several IC conditions. Graphical Abstract